BUDIDAYA CAISIN SECARA ORGANIK: PENGENDALIAN SERANGAN PATOGEN AKAR GADA DAN NEMATODA MELOIDOGYNE DENGAN PESTISIDA NABATI DARI DAUN PAHITAN - Hardjono Sri Gutomo; Pratignja Sunu; Trijono Djoko Sulistyo (Universitas Sebelas Maret, 2011)
Clubroot (Plasmodiophora brassicae Wor.) is an important obstacle in growing the brassicaceae, including chine cabbage. The infection of the pathogen is frequently complicated by Meloidogyne. This research was aimed to develop and evaluate the effectiveness of botanical pesticide with base material of leaf of Tithonia diversifolia Grey to control clubroot pathogen and Meloidogyne on chines cabbage grown by organic system. The research was conducted in Tawangmang, Karanganyar, Central Java from September until November 2010. The land used, was endemic area of clubroot and gall root of Meloidogyne. The experiment was consisted of 10 treatments arranged by randomized design with 3 replications. A unit treatment is a bed with area of 1x4 m2, high of 30 cm and the gap of between the bed by 50 cm. chines cabbage were planted with the distance of 10x10 cm. organic fertilizer amendment was applied the compost with dosage of 50 ton/ha (30 ton/ha a day before planting and 20 ton/ha on 14 days after planting), leaf of Tithonia with dosage of 0,5, 1,0, 1,5, and 2,0 ton/ha, and the frequency of 1 week before planting and 2 week after planting. The dependent variables were the disease intensity of clubroot, population of Meloidogyne, weigh of healthy lateral root, height of plant, weigh of crop yield, and weigh of dry biomass. The results suggested that the leaf extract of Tithonia could be effective to reduce population of the Meloidogyne spp., by the recommended that the leaf extract of Tithonia could be as a control component of complicated infection of clubroot pathogen and Meloidogyne spp. on growing the brassicaceae.